Evaluation of cortical bone perfusion using dynamic contrast enhanced ultrashort echo time imaging: a feasibility study - Wan, Lidi; Wu, Mei; Sheth, Vipul; Shao, Hongda; Jang, Hyungseok; Bydder, Graeme; Du, Jiang (Quantitative Imaging in Medicine and Surgery; Vol 9, No 8 (August 27, 2019): Quantitative Imaging in Medicine and Surgery, 2019)
Background: Dynamic contrast enhanced magnetic resonance imaging (DCE-MRI) has been used to study perfusion in a wide variety of soft tissues including the bone marrow. Study of perfusion in hard tissues such as cortical bone has been much more limited because of the lack of detectable MR signal from them using conventional pulse sequences. However, two-dimensional (2D) ultrashort echo time (UTE) sequences detect signal from cortical bone and allow fast imaging of this tissue. In addition, adiabatic 2D inversion recovery UTE (IR-UTE) sequences can provide excellent signal suppression of soft tissues, such as muscle and marrow, and allow cortical bone to be seen with high contrast and reduced artefacts. We aimed to assess the feasibility of using 2D UTE and 2D IR-UTE sequences to perform DCE-MRI in the cortical bone of rabbits and human volunteers. Methods: Cortical bone perfusion was studied in rabbits (n=12) and human volunteers (n=3) using 2D UTE and 2D IR-UTE sequences on a clinical 3T scanner. Dynamic data with an in-plane resolution of ~0.5×0.5 mm2, single slice thickness of 3 mm for rabbits and 10 mm for human volunteers, and temporal resolution of 23 s for 2D UTE imaging of rabbits, 28 s for 2D UTE imaging of human volunteers, and 60 s for 2D IR-UTE imaging of both the rabbits and human volunteers were acquired before and after the injection of a Gd contrast agent (Gd-BOPTA: Multihance; Bracco Imaging SpA, Milan, Italy). The dose was 0.06 mmol/kg for rabbits and 0.2 mmol/kg for human subjects. Kinetic analyses based on the Brix model, as well as simple calculations of maximum enhancement (ME) and enhancement slope (ES), were performed. Results: The 12 rabbits showed a mean Ktrans of 0.36±0.07 min−1, Kep of 8.42±3.17 min−1, ME of 28.30±6.83, ES of 0.35±0.18 for the femur with the 2D UTE sequence, and a mean Ktrans of 0.45±0.10 min−1, Kep of 9.80±0.50 min−1, ME of 48.84±12.12, and ES of 0.69±0.27 for the femur with the 2D IR-UTE sequence. Lower ME and ES values were observed in the tibial midshaft of healthy human volunteers compared to rabbits. Conclusions: These results show that 2D UTE and 2D IR-UTE sequences are capable of detecting dynamic contrast enhancement in cortical bone in both rabbits and healthy human volunteers. Clinical studies with these techniques are likely to be feasible.